Pengaruh Physical Evidence dan Kualitas Pelayanan terhadap Kepuasan Wisatawan Berkunjung di Wisata Alam Tirtosari View Lumajang - Saputri, Nella Yoana; Aini, Yulis Nurul (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to analyze the physical evidence and service quality of Tirtosari View Nature Tourism and their impact on visitor satisfaction. Tirtosari View Nature Tourism offers physical evidence and service quality to its visitors. This research is a descriptive quantitative study with variables including physical evidence, service quality, and visitor satisfaction. Data collection techniques used are questionnaires, observation, and documentation. The questionnaires were distributed using probability sampling with the simple random sampling method, resulting in 100 respondents who visited Tirtosari View Nature Tourism in Lumajang. The data analysis employed includes hypothesis testing and multiple linear regression analysis. The analysis results indicate that both physical evidence (X1) and service quality variables partially and simultaneously influence visitor satisfaction at Tirtosari View Nature Tourism in Lumajang. This is evidenced by the coefficient of determination result of 0.657, which means that there is a positive and significant influence of physical evidence and service quality on visitor satisfaction by 65.7%, with the remaining percentage explained by other factors outside this study. The hypothesis test results for the physical evidence variable (X1) show that tvalue (9.781) ttable (1.984) and significance value 0.015 0.05, and for the service quality variable (X2), tvalue (13.067) ttable (1.984) and significance value 0.000 0.05. Simultaneously, the hypothesis test results show Fvalue (170.748) Ftable (3.09) and significance value 0.000 0.05, meaning the hypothesis in this study rejects Ho and accepts Ha. From the results of this study, it is concluded that the physical evidence and service quality can be enhanced by the management of Tirtosari View Nature Tourism through improved facilities and friendly service, ensuring that visitors feel satisfied when visiting Tirtosari View Nature Tourism.